Culture and body image: subcultural variations in coping strategies and their associations with psychological distress among European Canadians and East Asian Canadians - Wojcik, Leah Rose; Masuda, Takahiko (Frontiers in Psychology, 2025)
Whether through friends, family, or social media, it is common to encounter situations that threaten body image. Threats to body image can lead individuals to question or perceive their appearance negatively if not coped with effectively. In turn, a negative body image is often associated with disordered eating patterns. Given the prevalence and severity of eating disorders globally, it is essential to gain insight into body image coping strategies to recognize adaptive ones while identifying those that may exacerbate body image concerns. With the significant cultural and ethnic diversity present in Canada, we investigated how two major ethnic groups cope with threats to their body image. We highlighted the importance of collecting data from underrepresented populations in psychological research and investigating nuanced variations across subgroups in multicultural societies. Participants included European Canadians (n = 156) and East Asian Canadians (n = 157) who rated the extent to which they used certain coping strategies in response to a body image threat. Cultural differences were examined in the usage of three coping strategies: appearance Fixing, Avoidance, and Positive Rational Acceptance. Linear regression analyses were conducted to explore relationships between the coping strategies and symptoms of stress, depression, and social anxiety. Results revealed a main effect of Culture on Appearance Fixing, with European Canadians more likely to endorse this strategy than East Asian Canadians when facing threats to body image. Conversely, East Asian Canadians tended to use Positive Rational Acceptance more than their European Canadian counterparts. In addition, we reported that overall, Appearance Fixing and Avoidance positively predicted symptoms of stress, depression, and social anxiety, and Positive Rational Acceptance emerged as a healthier way to cope, supporting the findings of similar previous works. The implications of culturally grounded research on body image and wellbeing are further discussed.